Changing industrial production systems and regional development in the New Europe - Hudson, R. (Transactions of the Institute of British Geographers, 2002)
The continuing expansion and deepening integration of the European Union is redefining the map of threats and opportunities for both companies and regions in Europe. In this paper I analyze the changing geography of the production system in three industries – automobiles, clothing and steel – as a product of the strategies and tactics of companies, states (at EU, national and regional levels) and trades unions, as they seek to shape geographies of production to favour their interests within this changing European political–economic space. It is argued that the end product of this process will be the creation of new and sharper forms of regional uneven development and qualitative differentiation between regions, as well as a renewed widening rather than further narrowing of regional differences in economic performance and well–being.
EPrint Processing Status: Full text deposited in DRO
Keywords: Automobile; Clothing; Steel; Regional difference; Economic development; European Union.